Analysis of Leverage Finance Company Oil & Gas Registered on the Indonesian Stock Exchange - Veronica , Nia; Nofal, Muhammad; Rianty Bidin, Cici; Fera (Universitas Muhammadiyah Pontianak, 2026)
This study examines the determinants of financial leverage in oil and gas companies listed on the Indonesia Stock Exchange. The objective is to analyze the effects of profitability, company growth, asset structure, and firm size on leverage measured by the Debt-to-Asset Ratio (DAR). Using panel data from 14 companies during 2022–2025 (56 observations), the study applies a Random Effects Model. The results show that only asset structure (tangibility) has a positive and significant effect on leverage, while profitability, growth, and firm size are insignificant. These findings imply that tangible assets are the primary consideration in debt financing decisions within Indonesia’s oil and gas industry.